Communication Network for Ultrasonic Acoustic Water Leakage Detectors - Awwad, Ameen (2020)
Water leaks in the distribution network produce significant losses and cause serious economic inconvenience especially in areas with water shortage. In this paper, the operational aspects of the most popular offline detection technologies, ground penetrating radars (GPR’s), infrared (IR) cameras, and acoustic detectors, were compared. The authors also studied the potential of using the recent Terahertz imaging technology for the same application. Acoustic detectors were found the most suitable technology for the atmosphere in UAE, where the levels of humidity and, consequently, soil moisture are high, because both of GPRs and IR cameras operational capability to detect leaks tend to decrease sharply as soil moisture increases. On the other side, a conventional acoustic detector has very limited scope of detection. This paper presents a method of expanding the sensing component of acoustic detectors by connecting acoustic sensors through a digital communication system using the 3G/4G networks to a monitoring center with an acoustic spectrum analyzer. The novelty of this system is its ability to provide offline detection of leakages in the underground water pipelines remotely without deforming the surrounding environment or adjusting the acoustic detector's analyzing system. Simulation results proves the ability of the system to reconstruct the input noise signal at the end of the proposed network which is to be connected to the acoustic analyzer.